WORD FORMATION AS STYLISTIC RESOURCE IN RAP MUSIC LYRICS: EVIDENCE FROM ICE CUBE S DEATH CERTIFICATE 1991 - Wongkar, Keysha Alsa; Lalu, Nanda Yohana Gabriela; Mogea, Tini; Pabur, Herminus Efrando (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Rap lyrics creatively express identity and culture through unique word choices yet few studies have examined how word formation shapes their rhythm and social meaning This study explores how Ice Cube s Death Certificate< em> album reflects identity culture and resistance through creative word formation This study aims to identify and analyze the word formation processes in Ice Cube s Death Certificate< em> album and to explain how these processes shape meaning and reflect cultural expression The research used a qualitative descriptive method and Yule s 2019 theory of word formation processes as the analytical framework The data were taken from official lyrics of three songs in Ice Cube s Death Certificate< em> album such as Steady Mobbin < em> True to the Game< em> and No Vaseline < em>and analyzed using document and content analysis techniques The findings showed that clipping and compounding were the most common word formation processes in Ice Cube s Death Certificate< em> album while borrowing blending acronyms coinage and derivation were used less often The frequent use of clipping shows that Ice Cube likes to make his words shorter to match the rhythm and sound more natural in everyday speech especially in African American Vernacular English AAVE Compounding helps Ice Cube create strong and meaningful words like motherfucker< em> and homeboys< em> that show identity culture and closeness in his community The other word formation types appear less often but still make the lyrics more creative and give deeper meaning to the songs These results indicate that Ice Cube intentionally used word formation to strengthen his artistic style cultural identity and social commentary showing that rap lyrics are not only entertainment but also a rich form of linguistic and cultural expression < p>